Caregivers' burden and its influencing factors among parents of children with asthma and comorbidities: a cross-sectional study - Yi, Xin; Sunzi, Kejimu; Liu, Jie; Yang, Fang; Wu, Xia; Bi, Dan; Huang, Qin; Dai, Lifei (Frontiers in Public Health, 2025)
ObjectiveThis study aims to investigate the current status of caregiver burden among parents of children with asthma comorbidities and to identify its associated factors.MethodsWe conducted a cross-sectional study from May to July 2025, involving 325 parents of children with asthma and comorbidities from two tertiary hospitals in Sichuan Province, China. Sociodemographic and clinical characteristics were collected through structured questionnaires. The Zarit caregiver burden interview (ZBI) and perceived social support scale (PSSS) were used to assess caregiver burden and social support levels, respectively. Statistical analyses included Pearson correlation, t-tests, analysis of variance (ANOVA), and multiple linear regression.ResultsThe total caregiver burden score was 40.44 ± 6.86, with 61.8% of the parents experiencing a moderate level of burden. Perceived social support was negatively correlated with caregiver burden (r = −0.621, P < 0.01). Multiple linear regression analysis revealed the child's age, asthma course, asthma comorbidity course, number of comorbidities, payment methods of healthcare costs, employment status, asthma control status, and perceived social support as factors significantly associated with caregiver burden, collectively explaining 55.2% of the total variance. This indicates that nearly half of the variance in caregiver burden could not be explained.ConclusionsThe caregiver burden among parents of children with asthma and comorbidities is substantial. Factors associated with higher burden levels include longer asthma course, greater number of comorbidities, longer comorbidity course, part-time employment status, and poor asthma control. Conversely, higher levels of perceived social support, older child age, and medical insurance and commercial insurance coverage were associated with lower burden levels. These findings provide an empirical basis for clinical institutions, communities, and relevant departments to inform the development of targeted interventions aimed at alleviating this caregiver burden. It should be noted that this study employed a cross-sectional design, and future longitudinal research is needed to verify causal relationships.